CREATIVITY INNOVATION OF MOTIVATIONAL T-SHIRTS AT “M T-SHIRT” SURABAYA - Giri Pamungkas; Cahaya Adinda Putri Ayu; Lidya Putri Nanda; M. Afif Sholehuddin; Yuli Kurniawati (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to describe the creativity designed for the invention of motivational t-shirts at "M T-Shirt" Surabaya. This type of research is descriptive using a qualitative paradigm. Data were analysed using domain analysis and taxonomic analysis. What will happen is the research finds that the inventions made by the "M T-Shirt" are emphasized in the creativity designed for the "M T-Shirt" T-shirt. The creativity used by "M T-Shirt" is to use interesting motivational words. As a result, the owner of this "M T-Shirt" is looking for new perspectives on popular figures. The creativity was applied to the "M T-Shirt" t-shirt design in the form of a theme that motivates all circles. This theme aims to attract consumers